Aspartate-β-hydroxylase (ASPH): A potential therapeutic target in human malignant gliomas. Issue 12 (December 2016) - Sturla, Lisa-Marie; Tong, Ming; Hebda, Nick; Gao, Jinsong; Thomas, John-Michael; Olsen, Mark; de la Monte, Suzanne M.
Abstract: Background: Despite therapeutic advances, survival with glioblastoma multiforme (GBM) remains below 15 months from diagnosis due to GBM's highly infiltrative nature which precludes complete surgical resection. Patient outcomes could potentially be improved by targeting genes and pathways that drive neoplastic cell motility and invasiveness, including hypoxia-inducible factor-1 (HIF-1α), NOTCH, and aspartate-β-hydroxylase (ASPH). Methods: Human astrocytoma biopsy specimens (n = 37), WHO Grades II–IV, were analyzed for levels and distributions of ASPH and HIF-1α immunoreactivity by immunohistochemical staining, and ASPH, Notch, JAG, HES1, HEY1 and HIF1α mRNA expression by quantigene multiplex analysis. The effects of small molecule inhibitors on ASPH's catalytic activity, cell viability and directional motility were examined in vitro in established GBM cell lines and primary tumor cells from an invasive mouse model of GBM. Results: The highest grade astrocytoma, i.e. GBM was associated with the highest levels of ASPH and HIF1α, and both proteins were more abundantly distributed in hypoxic compared with normoxic regions of tumor. Furthermore, mining of the TCGA database revealed higher levels of ASPH expression in the mesenchymal subtype of GBM, which is associated with more aggressive and invasive behavior. In contrast, lower grade astrocytomas had low expression levels of ASPH and HIF1α. In vitro experiments demonstrated that small molecule inhibitors targeting ASPH's catalytic activity significantly reduced GBM viability and directional motility. Similar effects occurred in GBM cells that were transduced with a lentiviral sh-ASPH construct. Conclusion: This study demonstrates that increased ASPH expression could serve as a prognostic biomarker of gliomas and may assist in assigning tumor grade when biopsy specimens are scant. In addition, the findings suggest that GBM treatment strategies could be made more effective by including small molecule inhibitors of ASPH.